Calistung assistance and training students through the Program Kampus Mengajar - Fitriyani, F.; Hadiapurwa, Angga (Universitas Pendidikan Indonesia, 2023)
In Indonesia, there is an Independent Campus Learning Curriculum (MBKM) which aims to produce graduates who are competent in various fields of knowledge and skills. The Teaching Campus Program is in the context of education in remote areas that lack supporting facilities and significant educational disparities. Reading, writing, and arithmetic (Calistung) skills are essential to education. However, at the UPTD SD NEGERI 2 Cantigi Kulon, this is a problem because students' Calistung skills could be higher based on observations and interviews with the school. To overcome this problem, the student team in the Teaching Campus program carried out mentoring and training activities as a concrete step in overcoming students' difficulties in reading, writing, and arithmetic abilities, as well as helping students and teachers in the learning process to improve Calistung abilities as the basis of literacy and numeracy. This service uses mentoring and training methods. As a result of this activity, students experienced increased reading, writing, and arithmetic skills. With a directed approach and the proper support, students can overcome obstacles in Calistung and achieve better academic achievement.